2021
DOI: 10.1016/j.ceramint.2021.02.205
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between degree of crystallinity and bluing of Zn1–Co Al2O4 (0≤x≤1) nanopowders prepared by soft chemistry route

Abstract: Correlation between degree of crystallinity and bluing of Zn 1-x Co x Al 2 O 4 (0≤x≤1) nanopowders prepared by soft chemistry route, Ceramics International, https://doi.org/10.1016/ j.ceramint.2021.02.205. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Magnesium aluminate (MgAl 2 O 4 ) had a small density, excellent strength at room and high temperature, and good resistance toward chemical attack [24]. Jabbar et al [25] announced that Zn 0.5 Co 0.5 Al 2 O 4 exhibited a larger surface area than that of CoAl 2 O 4 . Yuvaraj et al [26] reported that doping ZnAl 2 O 4 with Mg improved the thermal stability and superparamagnetic behavior compared to ZnAl 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium aluminate (MgAl 2 O 4 ) had a small density, excellent strength at room and high temperature, and good resistance toward chemical attack [24]. Jabbar et al [25] announced that Zn 0.5 Co 0.5 Al 2 O 4 exhibited a larger surface area than that of CoAl 2 O 4 . Yuvaraj et al [26] reported that doping ZnAl 2 O 4 with Mg improved the thermal stability and superparamagnetic behavior compared to ZnAl 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[48] Citrate gel method was used to prepare Zn 1Àx Co x Al 2 O 4 pigments. [49] The preparation of Zn 1Àx Co x Al 2 O 4 (0 Â 1) nanoceramic pigments consist of dissolving the following metallic nitrates in stoichiometric proportions: Co(NO 3 ) 2 •6H 2 O, Zn(NO 3 ) 2 •6H 2 O and Al(NO 3 ) 3 •9H 2 O. Citric acid (CA) was added to the mixture as a complexing agent with a molar ratio (CA/ Cations) equal to 3. The pH was adjusted to 7 with an ammonia solution.…”
Section: Application To the Preparation Of Aluminatesmentioning
confidence: 99%